EKSPLORASI ETNOBOTANI TANAMAN SINGKONG PADA SUKU TOBELO SEBAGAI PANGAN ALTERNATIF LOKAL DALAM MENDUKUNG KETAHANAN PANGAN - Hi Panu, Rasmi; Juma, Yusri; Ishak, Ismat; Purnomo, Eko (Department of Biology, Faculty of Mathematics and Natural Sciences, Hasanuddin University, 2026)
Cassava plants are optimally utilized from the stems, leaves, and tubers. However, traditional processed products of the Tobelo tribe are starting to be replaced. This study aims to determine the knowledge of the Tobelo people regarding the use of cassava plants and their contribution to supporting food security in North Maluku. This study uses a descriptive qualitative approach with a survey method. The sampling technique used is purposive sampling. This technique was chosen based on the research data needs, which require data on the understanding of cassava among the Tobelo people. The instruments used were interviews and documentation. The interviews consisted of four topics: the Tobelo people's understanding of cassava plants (varieties, morphology, and cultivation), its use in traditional rituals, management techniques, and aspects of its preservation. The results show that the Tobelo people have an understanding of agroecology that has been used for generations to preserve cassava as a staple food commodity. Traditional processed products are divided into three categories: staple foods, snacks or cakes, and foods that can be used long-term. However, there are several processed products such as cassava flour, ongol-ongol, and sinole that are starting to disappear. The calculated utility value was 0.54, indicating that the plant is still considered highly useful. In conclusion, the Tobelo people's understanding of cassava processing and cultivation supports national food security. Kata kunci : Cassava Plant, Tobelo Tribe, Traditional, Food Security